Relationship between nugent score and vaginal epithelial exfoliation - Amegashie, Courtney P.; Gilbert, Nicole M.; Peipert, Jeffrey F.; Allsworth, Jenifer E.; Lewis, Warren G.; Lewis, Amanda L. (PLOS ONE, 2017)
Objective Clue cells characteristic of bacterial vaginosis (BV) are thought to arise due to exfoliation of the vaginal epithelium; however, there is little published data connecting total numbers of epithelial cells to markers of BV. The purpose of this study was to enumerate exfoliated epithelial cells (independent of clue cells) and examine the relationship to Nugent score. Study design We conducted a cross-sectional sub-study of the Contraceptive CHOICE Project cohort. Vaginal swabs were used to create vaginal smears for Gram staining and these smears were later scored using the Nugent method, and then two blinded observers used microscopy to enumerate exfoliated epithelial cells. The degree of epithelial cell exfoliation was compared between women diagnosed as BV-negative (Nugent score 0–3), BV-intermediate (Nugent score 4–6), and BV-positive (Nugent score 7–10). BV specimens (Nugent 7–10) were randomly matched to specimens in the two other groups (Nugent low and Nugent-intermediate), in order to avoid comparing groups of women with potentially confounding baseline demographics. Results Exfoliated epithelial cell counts were higher in the vaginal smears from BV-positive women compared with BV-negative women. Higher levels of epithelial exfoliation were also evident in BV-intermediate women compared to those with low Nugent scores. After adjustment for clustering introduced by matching, the incidence ratio of increased epithelial cell counts was 2.09 (95% CI 1.50–2.90) for the BV-intermediate women and 1.71 (95% CI 1.23–2.38) for the BV positive women. Conclusion A vaginal epithelial exfoliation phenotype was measured in both Nugent-defined BV-positive and BV-intermediate women. Bacterial vaginosis and intermediate status (Nugent score >3) was associated with significantly more vaginal epithelial exfoliation compared to women with Lactobacillus-dominated microbiotas (Nugent 0–3).